Hatchet - Paulsen, Gary. (New York : Aladdin Paperbacks, 2006)
After a plane crash, thirteen-year-old Brian spends fifty-four days in the wilderness, learning to survive initially with only the aid of a hatchet given him by his mother, and learning also to survive his parents' divorce.
First Aladdin Paperbacks edition: 1996.
Revised cover edition: 1999.
Includes a readers guide (p. 182-186)
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Juvenile fiction; Divorce -- Juvenile fiction; Wilderness survival -- Juvenile fiction; Canada -- Juvenile fiction